Cu-exchanged RTH-type zeolites for NH3-selective catalytic reduction of NOx: Cu distribution and hydrothermal stability. Issue 1 (26th November 2018) - Shan, Yulong; Shi, Xiaoyan; Du, Jinpeng; Yu, Yunbo; He, Hong
Abstract : The Cu-exchanged RTH-type zeolites (Cu-RTH) were applied in ammonia-selective catalytic reduction (NH3 -SCR) of NO x . Abstract : The Cu-exchanged RTH-type zeolites (Cu-RTH) were applied in ammonia-selective catalytic reduction (NH3 -SCR) of NO x . The effects of Cu loading and distribution on the NO x reduction efficiency were investigated. The hydrothermal stabilities of a series of Cu-RTH catalysts were also presented. Excellent NO x conversion activity was observed for Cu-RTH catalysts with high Cu loadings (2.5–4.4 wt%) in the temperature range from 150 °C to 550 °C. Two possible sites (α and β species) for Cu 2+ species were proposed based on the analysis of H2 -TPR and DRIFTS results. The α species next to the 8-membered rings showed significantly higher TOF (turnover frequency) of NO conversion than the β species present next to the rth cage. The Cu-RTH catalysts showed lower activation energies (30–40 kJ mol −1 ) compared with that of the Cu-SSZ-13 catalyst (∼54 kJ mol −1 ) due to the different zeolite framework structures. After undergoing hydrothermal aging, although the zeolite framework structure stayed stable, the active Cu 2+ species migrated to inactive sites, which resulted in the loss of NO x conversion for the NH3 -SCR reaction. The saturated Cu 2+ -exchanged Cu4.4 -RTH catalyst showed the best hydrothermal stability due to the limited Cu 2+ mobility, which stabilized the active Cu 2+ species.